Influence of different concentration of heavy metals on the seed germination and growth of tomato - Mami, Yaqvob; Ahmadi, Golale; Shahmoradi , Masoud; Ghorbani, Hamid Reza (Global Journal of Food and Agribusiness Management, 2019)
Some heavy metals in higher doses may cause metabolic disorders and growth inhibition for most of the plant species. This study was performed in order to evaluate two tomato varieties (Barakat and Local tomato) response to ordinary Heavy Metals (Fe, Pb and Cu) in northern of Iran. Five doses (0, 0.001, 0.01, 0.1 and 1%) of lead acetate, cupric carbonate and ferric chloride were investigated. The experiment was conducted under 12±2h photoperiodic laboratory condition in a laboratory germinator. Results showed that the reaction of varieties to different heavy metal compounds and those doses is varied and Barakat variety has greater resistance in more indices. Also, heavy metals kind and different doses of these compounds affected the germination and some growth indices. In this experiment the highest inhibition on shoot length 2.66 cm, root/ shoot ratio 0.87, moisture content 0.31 g, fresh weight 0.32 g and dry weight 0.059 g were obtained from Fe compound, however; had not significance different with other heavy metal compounds in case of root length 3.39 cm and coefficient of germination velocity 0.27% (P≤0.05). Also, dose of 1% appeared highest undesirable effect on all evaluated indexes